Supplementation of Arjun (Terminalia arjuna) bark powder prevented oxidative stress and enhanced antioxidants in kidneys on isoproterenol-treated Swiss albino mice model - Rashedul Haque; Sajib Paul; Md. Tipu Sultan; Faizul Islam Chowdhury; Md. Kawser; Shariful Islam Nayan; S.M. Hafiz Hassan; Afsana Kabir Chowdhury; Raiyana Huda; Sauda Sumaya Dina; Sheikh Zahir Raihan (Clinical Nutrition Open Science)
Summary: This study aimed to investigate the impact of Arjun on the oxidative stress levels in the renal system. Oxidative stress induces renal injury, resulting in a range of problems including renal damage, renal dysfunction, and chronic kidney disease. The objective of this study was to investigate the antioxidant properties and efficacy of Arjun in mitigating oxidative stress and renal damage induced by isoproterenol. A total of twenty-four mice were divided into four groups, with each group consisting of six mice. The body weight of each mouse in the groups was recorded daily. The weight of the organ, such as the kidney, while it was wet, was also recorded. Plasma levels of creatinine and uric acid were assessed using biochemical analysis. Plasma and kidney samples were analyzed to assess MDA, NO, and MPO levels as indicators of oxidative stress. Creatinine plasma (ISO- 1.6043 mg/dL, ISO + Arjun 2.5%- 1.4124 mg/dL, P = 0.0081) and in uric acid plasma (ISO- 3.2201, ISO + Arjun 2.5%- 2.8033, P = 0.0057). MDA plasma (ISO- 7.9600 nmol/mL, ISO + Arjun 2.5%- 5.0467 nmol/mL, P = 0.0070) and in MDA kidney (ISO- 29.7000 nmol/g tissue, ISO + Arjun 2.5%- 23.1667 nmol/g tissue, P = 0.0048). NO plasma (ISO- 9.5067 nmol/mL, ISO + Arjun 2.5%- 6.8800 nmol/mL, P = 0.0072) and in NO kidney (ISO- 192.2000 nmol/g tissue, ISO + Arjun 2.5%- 98.3667 nmol/g tissue, P = 0.0070). MPO plasma (ISO- 32.793 U/min/mL, ISO + Arjun 2.5%- 23.586 U/min/mL, P = 0.0041) and in MPO kidney (ISO- 121.950 U/min/mg protein, ISO + Arjun 2.5%- 79.492 U/min/mg protein, P = 0.0100). Catalase plasma (ISO- 15.90 U/min, ISO + Arjun 2.5%- 19.75 U/min, P = 0.0070) and in catalase kidney (ISO- 381.6 U/min/g protein, ISO + Arjun 2.5%- 581.9 U/min/g protein, P = 0.0082). SOD plasma (ISO- 22.667 U/min, ISO + Arjun 2.5%- 26.8000 U/min, P = 0.0080) and in SOD kidney (ISO- 60.9667 U/min/g protein, ISO + Arjun 2.5%- 91.1333 U/min/g protein, P = 0.0033). Ultimately, a histopathological examination was conducted on the kidney specimens, which were subjected to Hematoxylin and Eosin staining. Administration of isoproterenol led to cell infiltration in the kidney, while therapy with Arjun resulted in improved renal imaging. To summarize, it may be inferred that the antioxidant properties of Arjun mitigated the oxidative stress induced by isoproterenol in the kidney.